Gestión de Talento Humano en la Cooperativa de Ahorro y Crédito Chibuleo en la Cuidad de Babahoyo, Periodo 2023. - Monserrate Monserrate, Estefany Michelle (2024)
The case study on human talent management at the Chibuleo Savings and Credit Cooperative in Babahoyo during 2023 focuses on understanding and evaluating its practices and strategies. Its relevance lies in providing insights to improve and strengthen human capital management. It benefits the research community by offering a concrete case for future research in business management and human resources. It also benefits the academic community by enriching the teaching process with tangible examples. Companies and entrepreneurs find it useful to obtain knowledge about successful strategies and areas of opportunity in human talent management. Limiting the scope to a particular case makes it easier to collect relevant data and identify specific trends. Collaboration with the cooperative guarantees the viability and quality of the study by having access to verifiable and updated information. This specific and collaborative approach ensures concrete and applicable results in different business environments.